2013
DOI: 10.1002/acr.22021
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Yellow Fever 17D Vaccine in Adults Receiving Systemic Corticosteroid Therapy: An Observational Cohort Study

Abstract: Objective. To assess the safety and immunogenicity of live attenuated yellow fever (YF) 17D vaccine in adults receiving systemic corticosteroid therapy. Methods. All adult travelers on systemic corticosteroid therapy who had received the YF17D vaccine in 24 French vaccination centers were prospectively enrolled and matched with healthy controls (1:2) on age and history of YF17D immunization. Safety was assessed in a self-administered standardized questionnaire within 10 days after immunization. YF-specific neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
1
32
0
5
Order By: Relevance
“…One study found no effect on responses to yellow fever vaccine. 170 Chronic inhaled steroids did not impair responses to influenza vaccine in another study. 171 …”
Section: Diagnosismentioning
confidence: 92%
“…One study found no effect on responses to yellow fever vaccine. 170 Chronic inhaled steroids did not impair responses to influenza vaccine in another study. 171 …”
Section: Diagnosismentioning
confidence: 92%
“…The VIHVO cohort is restricted to French HIV-infected migrants, which may limit the external validity of our results, as is the case of many vaccinal studies [8][9][10]. Further investigations are thus needed to determine if our conclusions also apply to HIV-infected patients in general or even to all immunocompromised patients, not just those infected by HIV.…”
Section: Discussionmentioning
confidence: 80%
“…HIV-infected persons may have suboptimal primary and longterm responses to vaccines [8][9][10][11]. Moreover, immigrants may have an incomplete vaccine schedule because of their migratory life course [12].…”
Section: Introductionmentioning
confidence: 99%
“…Suppressed HIV viral load at the time of immunisation also influenced durability of neutralising antibodies titres at long-term follow-up [41]. There are no large studies available to assess the efficacy and safety of YFV in non-HIV ICH although available observational data with small numbers of SOT patients and those on long term steroid therapy showed that no major adverse event occurred and neutralizing antibodies were detected with 17-D vaccine [42,43]. A successful vaccine response has also been reported in a patient with allo-HSCT who received primary vaccination 8 years post-transplant [44].…”
Section: Yellow Fever Vaccinementioning
confidence: 92%